2021
DOI: 10.3390/clockssleep3040041
|View full text |Cite
|
Sign up to set email alerts
|

GI-SleepNet: A Highly Versatile Image-Based Sleep Classification Using a Deep Learning Algorithm

Abstract: Sleep-stage classification is essential for sleep research. Various automatic judgment programs, including deep learning algorithms using artificial intelligence (AI), have been developed, but have limitations with regard to data format compatibility, human interpretability, cost, and technical requirements. We developed a novel program called GI-SleepNet, generative adversarial network (GAN)-assisted image-based sleep staging for mice that is accurate, versatile, compact, and easy to use. In this program, ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Delimayanti et al ( 23 ) demonstrated the utilization of features extracted from EEG signals via FFT to improve the performance of automated sleep stage classification through machine learning methods. Gao et al ( 24 ) developed a novel program called GI-SleepNet, a generative adversarial network (GAN)-assisted image-based sleep staging for mice that is accurate, versatile, compact, and easy to use. Loh et al ( 25 ) proposed a deep learning model based on a one-dimensional convolutional neural network (1D-CNN) for CAP detection and homogenous 3-class classification for sleep stages: wakefulness (W), rapid eye movement (REM), and NREM sleep.…”
Section: Related Workmentioning
confidence: 99%
“…Delimayanti et al ( 23 ) demonstrated the utilization of features extracted from EEG signals via FFT to improve the performance of automated sleep stage classification through machine learning methods. Gao et al ( 24 ) developed a novel program called GI-SleepNet, a generative adversarial network (GAN)-assisted image-based sleep staging for mice that is accurate, versatile, compact, and easy to use. Loh et al ( 25 ) proposed a deep learning model based on a one-dimensional convolutional neural network (1D-CNN) for CAP detection and homogenous 3-class classification for sleep stages: wakefulness (W), rapid eye movement (REM), and NREM sleep.…”
Section: Related Workmentioning
confidence: 99%
“…Alternatively, MC-SleepNet combines two types of deep neural networks that can automatically score sleep stages with an accuracy of 96.6% [2] , whereas mixture z-scoring, a machine learning algorithm used in AccuSleep, demonstrated an accuracy of 96.8% [3] . A very high accuracy of determining sleep stages was also achieved with automated sleep stage scoring using a k-nearest neighbors classifier [4] , a supervised deep convolutional neural network called WaveSleepNet [5] , a generative adversarial network-assisted image-based sleep staging program named GI-SleepNet [6] , and a neural network architecture that is able to distinguish between the three main stages Wake, REM and NREM as well as the infrequent stages pre-REM and artifact [7] . Although the accuracy of automated sleep staging is excellent, analysis of sleep-wake cycles in mice remains a time-consuming and laborious process.…”
Section: Introductionmentioning
confidence: 99%